2021
DOI: 10.1080/19932820.2021.1943924
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin with lycopene modulates enzymic antioxidant genes pathway in isoproterenol cardiotoxicity in rats

Abstract: Quercetin (QN) is a naturally occurring phenolic compound found largely in vegetables and fruits. Lycopene (LY) is yet another natural phytocompound, found abundantly in red-colored fruits and vegetables. Both have been reported to have beneficial activities in humans. In this study, we document in vivo experimental model for isoproterenol (ISO) cardiac injury toxicity in Sprague-Dawley (SD) rats and treatment with a combined optimized concentration of quercetin and lycopene (QL). Male SD rats of different gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…All institutional and national guidelines for the care and use of laboratory animals were followed. The doses of quercetin, 27 telmisartan, 28 and 5-FU 29 were chosen depending on previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…All institutional and national guidelines for the care and use of laboratory animals were followed. The doses of quercetin, 27 telmisartan, 28 and 5-FU 29 were chosen depending on previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Flavonols have numerous cardioprotective properties, such as platelet stabilization, anti-inflammatory, antidiabetic, antihypertensive, and hypocholesterolemic activity [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. To the best of our knowledge, quercetin is the most widely distributed and well-known flavonol obtained from natural sources, as well as the best-studied flavonol, in both in vitro and in vivo studies [ 51 ].…”
Section: Flavonols and Their Cardioprotective Activitymentioning
confidence: 99%
“…Besides, other studies have shown that quercetin can be used in combination with other antioxidants to protect against ischemic injury [100,101]. The combined application of lycopene and quercetin improved myocardial ischemic injuries in a rat model [102]. In contrast with quercetin treatment (100 mg/kg b.w.)…”
Section: The Effects Of Lycopene On Ischemic and I/r Injuriesmentioning
confidence: 99%
“…Reducing cardiotoxicity (↓CK-MB, LDH, MYO, and TROP) and oxidative stress (↓MDA) via ↑GSTμ, SOD1, SOD2, CAT, and Bcl-2[102] …”
mentioning
confidence: 99%